Data centre essentials design, construction, and operation of data centres for the non-expert - Fogarty, Vincent; Flucker, Sophia (John Wiley & Sons, Inc., 2023)
"As prefaced, this book is written primarily for lawyers, financial and insurance advisors, surveyors, engineers, architects, and other professionals who do not necessarily have direct experience with data centres but need to participate in the subject matter. The intention is to provide the reader with the broad landscape of technical and commercial issues and help identify a high-level overview of critical considerations. We trust that the book should provide the key concepts and terminology to complement their core skills when drafting documents or making business decisions and help them ask more informed questions when working on data centre projects. Data centres are a complex ecosystem with many stakeholders from different disciplines interacting at different phases of the facility's lifetime. The objective of this text is to provide the reader with a full spectrum of the entire life cycle of a data centre from inception to operational use."--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on July 13, 2023)
Keywords: Data centers; Centres de traitement de l'information; computer centers